The Reality of Using Electronic Management From the Point of View of Basic School Principals in Deir Alla Directorate - Jordan in light of the Corona pandemic - Salem, Majed Khaleel (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the reality of using electronic management from the point of view of school principals of basic stage in Deir Alla Directorate – Jordan in light of the Corona Pandemic. The study used the descriptive and analytical method; the study sample consisted of (36) principals in the basic schools of Deir alla ; (100%) of the study population. To achieve the objectives of the study we used the questionnaire to measure the degree of the reality of the use of electronic management, the findings of the study were: the reality of the use of electronic management on a total average (4.10 out of 5), a high degree (high), and at the level of fields The field of training and qualification of school staff got the highest average (4.17), and the readiness of infrastructure and medium equipment (4.10) and thirdly: the role of the school principal in supporting electronic administration, with an average of (4.06) and the practice of basic school principals for strategic planning; Average (4.03) and all are rated (High), and The results showed that there were no statistically significant differences in the use of electronic management In light of the corona pandemic, from the point of view of basic school principals in Deir Alla the Directorate of Education due to the variable of (gender, educational qualification and experience), while the results revealed the existence of a difference according to the variable of job experience for 10 years and more, The study recommended the necessity of holding courses and seminars for school principals and organizing scientific meetings to enlighten them about contemporary issues related to laws and instructions with electronic administration, and on the mechanism of their implementation and planning, and to provide incentives for principals and administrators to encourage them to deal with e- learning and follow up teachers and students.